2004
DOI: 10.1152/ajplung.00340.2003
|View full text |Cite
|
Sign up to set email alerts
|

cAMP-stimulated Na+transport in H441 distal lung epithelial cells: role of PKA, phosphatidylinositol 3-kinase, and sgk1

Abstract: H441 cells, a bronchiolar epithelial cell line, develop a cAMP-regulated benzamil-sensitive Na+ transport pathway on permeable supports (Itani OA, Auerbach SD, Husted RF, Volk KA, Ageloff S, Knepper MA, Stokes JB, Thomas CP. Am J Physiol Lung Cell Mol Physiol 282: L631-L641, 2002). To understand the molecular basis for the stimulation of Na+ transport, we delineated the role of specific intracellular pathways and examined the effect of cAMP on alphabetagamma-epithelial Na+ channel (ENaC) and sgk1 expression. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
55
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(75 citation statements)
references
References 74 publications
17
55
2
1
Order By: Relevance
“…This was surprising since previous studies of H441 cells indicated that PI3K played a central role in the control of Na ϩ transport (51). However, the cells used in this earlier study displayed a Na ϩ -absorbing phenotype under basal conditions (51), whereas, in our hands, G Na is negligible in hormonedeprived cells (see also Ref.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…This was surprising since previous studies of H441 cells indicated that PI3K played a central role in the control of Na ϩ transport (51). However, the cells used in this earlier study displayed a Na ϩ -absorbing phenotype under basal conditions (51), whereas, in our hands, G Na is negligible in hormonedeprived cells (see also Ref.…”
Section: Discussioncontrasting
confidence: 64%
“…These observations are consistent with a body of data that highlights SGK1 as an important regulator of G Na in absorptive epithelia (1-3, 31, 49 -51, 53, 57). Although it is clear that glucocorticoid hormones do induce SGK1 expression (31), SGK1 is an important downstream target of PI3K (29), and data from several absorptive cell types have suggested that insulin can increase the apical abundance of ENaC via a mechanism dependent on a PI3K-mediated increase in SGK1 activity (2,8,46,51). Moreover, PIP 2 and PIP 3 also activate ENaC by binding to the channel complex, and this provides another mechanism by which PI3K-coupled agonists, such as insulin, can stimulate Na ϩ transport (20,42,43,52).…”
Section: Discussionmentioning
confidence: 99%
“…When cultured at air interface, these cells form an absorptive epithelial monolayer, exhibit vectorial ion transport processes and have similar morphological and phenotypic characteristics to primary cultured human airway epithelial cells (HBEC) and in vivo human airway [4,8,19]. Therefore, they have been used by us and a number of other researchers as a model of absorptive human airway epithelium [25,36,41,42]. The aim of this study was to use H441 cell monolayers to explore the process by which glucose diffuses across airway epithelium, to identify the function of GLUT transporters and the role of glucose metabolism in maintaining low glucose concentrations in human ASL.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that AhR induces signaling pathways that entail ERK, PKA, MMP9 and cAMP, cGMP and Ca 2+ [22]. It has also been shown that AhR is more sensitive to the cAMP signaling pathway [22,23], and that cAMP induces nuclear translocation of the AhR [24]. Thus it appears that the two signaling pathways for regulation of ENaC, cAMP, and cGMP are compartmentalized.…”
Section: Discussionmentioning
confidence: 99%